ʿAmaliyat Ta'līm Ḥifẓ al-Mufradāt bīwāsṭi al-Āghānīyah li-Tarjumah Kutub al-Turāth fī Maʿhad Mashāriq al-Anwār al-Islāmī li-l-Banāt bi Babakan Ciwaringin Cirebon - Miftahul Ula; Faliqul Isbah (ALSINATUNA, 2016)
The basic concept of Arabic language learning is learning kinds of noun. Therefore, it is necessary for Arabic language learners to know the name of things needed in communication. One of the causes of failure and success in language learning is the use of media. There are so many teaching media used in language learning, including songs. In this case, the teacher chooses the most favorite song of the students, and then changes its lyrics with difficult words of the classic book. This media is used because it is supposed to be able to create fun and enjoyable situation and give the students ease in memorizing new vocabularies, especially in understanding the meaning of the classic books. On the other hand, the weakness of this media is that the teacher, especially those who have lack of singing abilities, found any difficulties in preparing the vocabulary of the classic book and put them into the song lyrics.